2021
DOI: 10.1155/2021/8859358
|View full text |Cite
|
Sign up to set email alerts
|

Performance of Polypropylene Fiber‐Reinforced Solidified Soil

Abstract: Urgent repair and construction of airstrips is a research hotspot in global airport engineering. Selecting the proper structural materials is a key component of the airstrip repair process. First, with unconfined compressive strength and splitting tensile strength, the fiber length and content of polypropylene (PP) fiber-reinforced solidified soil were optimized. Then, using a scanning electron microscope, the reinforcing mechanism of PP fiber on soil and the influence mechanism of fiber parameters on fiber-re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…RE a brittle material having low flexural strength and poor damage resistance when compared to contemporary building materials, requires improvement in the engineering properties. All types of soils have poor resistance to tensile stresses; hence, reinforcing them with discrete fibres has shown a very impressive improvement in the behaviour of soils (Li et al 2014;Hu et al 2021;Wang and Hu 2019;Jiang, Cai, and Liu 2010). While stabilizers like cement can help achieve durability and strength enhancement properties, fibres can provide ductility by improving their tensile and flexural strength.…”
Section: Introductionmentioning
confidence: 99%
“…RE a brittle material having low flexural strength and poor damage resistance when compared to contemporary building materials, requires improvement in the engineering properties. All types of soils have poor resistance to tensile stresses; hence, reinforcing them with discrete fibres has shown a very impressive improvement in the behaviour of soils (Li et al 2014;Hu et al 2021;Wang and Hu 2019;Jiang, Cai, and Liu 2010). While stabilizers like cement can help achieve durability and strength enhancement properties, fibres can provide ductility by improving their tensile and flexural strength.…”
Section: Introductionmentioning
confidence: 99%
“…The test results showed that the soil particles were tightly bound under 3.5% content of SH polymer, and the impact resistance of the specimens reached the maximum when the glass fiber content was 3.0%. Hu [ 25 ] investigated the reinforcement mechanism of polypropylene (PP) fiber-reinforced consolidated soil and discussed the effect of fiber parameters on the mechanical properties of consolidated soil. It was finally concluded that PP fibers with a length of 12 mm and a fiber content of 0.3% have the best performance and economic cost.…”
Section: Introductionmentioning
confidence: 99%
“…During the hydration process, calcium aluminate hydrate (C-A-H) and calcium silicate hydrate gel (C-S-H) were produced, which improved soil conditions [9,10]. However, traditional OPC curing agents have problems such as limited mechanical strength, poor durability, poor volume stability, high pollution in the production process, and high CO 2 emissions [11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%